Cattlemen's Day 2019 - E. A. Boyle (Kansas Agricultural Experiment Station Research Reports, 2019)
Report for 2019 on Kansas beef cattle research, including cattle management, cattle nutrition, and meat science.
Keywords: Beef cattle